High performance diagnostics for Time-Of-Flight and X ray measurements in laser produced plasmas, based on fast diamond detectors. (19th December 2016) - Angelis, R. De; Consoli, F.; Verona, C.; Giorgio, G. Di; Andreoli, P.; Cristofari, G.; Cipriani, M.; Ingenito, F.; Marinelli, M.; Verona-Rinati, G.
Abstract: The paper reports about the use of single-crystal Chemical Vapour Deposited (CVD) diamonds as radiation detectors in laser-matter interaction experiments on the ABC laser in ENEA – Frascati. The detectors have been designed and realized by University of Tor Vergata – Rome. The interdigital configuration and the new design of the bias-tee voltage supply units guarantee a fast time response. The detectors are sensitive to soft-X photons and to particles. A remarkable immunity to electromagnetic noise, associated with the laser-target interaction, makes them especially useful for the measurements of the time of flight of fast particles. A novel diamond assembly has been tested in plasmas generated by the ABC laser in the nanosecond regime at intensities I =10 13÷ 14 W/cm 2, where contributions from X rays, fast electrons and ions could be observed.